Need Analysis Of CEFR Based Multisensorial Listening Activities For Middle School Students In Cirebon - Ahmad Rifai; Lisa Nurhasanah; Siti Luruh Ayu Noerjanah (STIT Buntet Pesantren Cirebon, 2025)
This study explores the conceptual characteristics and classroom-based needs of implementing multisensory listening instruction aligned with the CEFR (Common European Framework of Reference) assessment. Using a qualitative needs analysis approach, the study aims to answer two research questions: (1) What are the characteristics of multisensory listening learning through the CEFR assessment? and (2) How are teachers and students’ needs in teaching and learning multisensory listening through the CEFR assessment? The data were collected through conceptual synthesis of relevant literature and semi-structured interviews with two English teachers and two students at MTs Mafatihul Huda Cirebon, Indonesia. Findings revealed six core dimensions of multisensory listening: multimodal sensory engagement, emotional and motivational activation, cognitive-metacognitive scaffolding, technological and game-based facilitation, inclusivity and differentiated learning, and real-world cultural grounding. These dimensions support CEFR descriptors related to listening comprehension, sociolinguistic competence, and pragmatic awareness. Interview data further highlighted the need for CEFR-based listening materials that are emotionally engaging, culturally relevant, and adapted to the technological and pedagogical realities of local classrooms. Teachers expressed the need for practical resources and training in CEFR-oriented listening assessment, while students emphasized the importance of visual, contextual, and relatable content. The study concludes that effective implementation of multisensory listening through the CEFR requires an integrated approach that combines curriculum design, teacher support, and localized material development. Keywords: multisensory listening, CEFR, needs analysis, EFL, listening comprehension, teacher–student perspectivesThis study explores the conceptual characteristics and classroom-based needs of implementing multisensory listening instruction aligned with the CEFR (Common European Framework of Reference) assessment. Using a qualitative needs analysis approach, the study aims to answer two research questions: (1) What are the characteristics of multisensory listening learning through the CEFR assessment? and (2) How are teachers and students’ needs in teaching and learning multisensory listening through the CEFR assessment? The data were collected through conceptual synthesis of relevant literature and semi-structured interviews with two English teachers and two students at MTs Mafatihul Huda Cirebon, Indonesia. Findings revealed six core dimensions of multisensory listening: multimodal sensory engagement, emotional and motivational activation, cognitive-metacognitive scaffolding, technological and game-based facilitation, inclusivity and differentiated learning, and real-world cultural grounding. These dimensions support CEFR descriptors related to listening comprehension, sociolinguistic competence, and pragmatic awareness. Interview data further highlighted the need for CEFR-based listening materials that are emotionally engaging, culturally relevant, and adapted to the technological and pedagogical realities of local classrooms. Teachers expressed the need for practical resources and training in CEFR-oriented listening assessment, while students emphasized the importance of visual, contextual, and relatable content. The study concludes that effective implementation of multisensory listening through the CEFR requires an integrated approach that combines curriculum design, teacher support, and localized material development.Keywords: multisensory listening, CEFR, needs analysis, EFL, listening comprehension, teacher–student perspectives